‘The Fantastic Underwater Life All Around Me:’ Female Water Spirits in Jeffrey Eugenides’s "Middlesex” - Leporini, Nicola (Amaltea. Revista de Mitocrítica, 2014)
‘The Fantastic Underwater Life All Around Me:’ Female Water Spirits in Jeffrey Eugenides’s "Middlesex”